Kinanthropometric and Physical Characteristics of Elite Freestyle Paddlers - Sandro Dias; Inês Caetano; Anthony Gorman (International Universities Strength and Conditioning Association, 2024)
The aim of this study was to explore the kinanthropometric and physiological profile of elite freestyle paddlers. A total of fifteen (male, n = 8; female, n = 7) elite GB Freestyle Kayak Team paddlers participating in the 2023 World Championship volunteered. Anthropometric data were collected on standing height, sitting height, arm span, and body mass. Additionally, field-based tests assessed several functionally relevant attributes: Leg and back flexibility was measured through the sit-&-reach test; handheld dynamometers measured bilateral handgrip strength and an isometric mid-thigh pull assessed lower limb and back strength; and overhead medicine ball throws were performed to gauge upper body power. Within and between-sex comparisons were explored using paired and independent samples t-tests respectively, and Hedges' g effect sizes were calculated to determine the magnitude of difference between conditions, reported as means ± SDs. Z-Scores for all parameters were individually calculated to assess participants in relation to grouped means. Male freestyle paddlers were taller and had greater sitting height and arm span than female paddlers. They were also functionally stronger and more powerful. Generally, freestyle paddlers have similar body proportions to slalom paddlers. Data from this study could be used as normative values for profiling, potentially outlining successful anthropometric and performance attributes. Even though freestyle paddling appears to depend heavily on strength and flexibility, more research is required to identify which performance metrics may be associated with better on-water freestyle performance.